The Effectiveness Of Gestalt Game Techniques To Improve The Honest Character Of Teenagers - Irianti, Rizky Anissa (Prosiding University Research Colloquium, 2021)
This study aims to test the effectiveness of the gestalt game technique to improve the honest character of teenager. This study uses the One Group Pretest Posttest Design. The samples taken in this study were 11 teenagers consisting of one experimental group. Sampling using random sampling technique. The method of collecting and using an honest character questionnare. The data analysis Paired sample t-test. The results of this study indicate that the gestalt game technique is effectivefor improving the honest character of teenager. This is evidenced by the results of the paired sample t-test with a probability value of sig (2-tailed) 0,001<0,05. Basedon the results of the analysis and discussion, there is a difference in the average score of the honest character questionnaire 9,80%, from the gestalt equation that is effective for improving the honest character of teenager.